2007
DOI: 10.1007/s10549-007-9871-6
|View full text |Cite
|
Sign up to set email alerts
|

Id-1 regulates Bcl-2 and Bax expression through p53 and NF-κB in MCF-7 breast cancer cells

Abstract: Although increasing evidence supports the protective role of inhibitor of differentiation and DNA binding-1 (Id-1) against anticancer drug-induced apoptosis, the underlying molecular mechanisms seem to vary depending on the tumor system. Here, we examined the direct role of Id-1 in MCF-7 breast cancer cells by ectopically overexpressing Id-1 under serum-free condition, where the endogenous Id-1 expression was suppressed. Id-1 expression resulted in increased number of viable cells, reduced Bax expression, enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…Id-1 seems to regulate many biological effects by p53 modulation. Recently, we showed that Id-1 regulates both bcl-2 and bax expressions through inhibition of p53 expression and has a protective effect on taxol-induced apoptosis (Kim et al, 2007a). Here, we also demonstrate that Id-1 inhibited PTEN expression and activated the Akt pathway through p53 regulation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Id-1 seems to regulate many biological effects by p53 modulation. Recently, we showed that Id-1 regulates both bcl-2 and bax expressions through inhibition of p53 expression and has a protective effect on taxol-induced apoptosis (Kim et al, 2007a). Here, we also demonstrate that Id-1 inhibited PTEN expression and activated the Akt pathway through p53 regulation.…”
Section: Discussionsupporting
confidence: 62%
“…In human breast epithelial cells, Id-1 enhances cyclin D1 and cyclin E expressions and affects CDK4 and CDK2 activities (Swarbrick et al, 2005). We have previously reported the enhancement of cell growth and induction of G 1 to S phase transition by ectopic Id-1 expression in MCF7 breast cancer cells (Kim et al, 2007a). In this study, our data show that Id-1 enhances the Akt-mediated Wnt/TCF pathway and cyclin D1 expression, a TCF/LEF response gene, and leads to Akt-mediated p27 Kip1 phosphorylation and its cytosolic retention in MCF7 breast cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Overexpression of Id proteins in embryonic-derived fibroblasts facilitates cell cycle S-phase under serum-deprived conditions [34], where Id-1 has been reported to induce the proliferation of cochlear sensory epithelial cells via the NF-kappaB/cyclin D1 pathway [35]. Furthermore, various cancer cell lines appear to require Id-1 and Id-2 expression for their growth, survival, and metastasis via regulation of p53 and PI3K/Akt/NF-kappaB signaling pathways in a similar fashion to that described for Twist-1 and Dermo-1 [36][37][38][39][40]. More recently, Id-1 has been shown to mediate long-term repopulating hematopoietic stem cell maintenance and inhibit myeloid differentiation [41,42].…”
Section: Discussionmentioning
confidence: 82%
“…The mechanism by which Id1 regulates the expression of β1-integrin is still not clear. Recently, it was reported that p53 expression may regulate the recycling of β1-integrin (25), and Id1 can regulate the expression of p53 (26). We propose that the interaction of Id1 and p53 is essential for Id1-mediated expression of β1-integrin, a possibility that will be addressed in future study.…”
Section: Discussionmentioning
confidence: 81%